Soft Drinks Intake is Associated with Obesity and Urine Disorders in Medical Students - Irfan Afzal Mughal, Shahida Parveen, Amna Faruqi, Muhammad Saqlain Azam, Muhammad Riaz Shahbaz Janjua, Asma Irfan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To determine the ramifications of soft drinks on Body Mass Index and effects on various renal parameters. Study design: Cross-sectional study Place and duration of study: HBS Medical and Dental College from 1st January 2020 to 31st December 2021. Methodology: One hundred and ten students from first year to final year MBBS were recruited from Medical Colleges of Islamabad. We assessed caffeinated sugar beverage consumption (Sprite, Mountain Dew, Coke, Pepsi & 7-Up). Inclusion criteria consisted of users (n=48) who took caffeinated soft drinks at least 5-7 glasses/week. Those who took less than this drink was labelled non-users (n=62). Questionnaire we used was self-administered about sociodemographic data, height, weight, soft drinks consumption frequency, and a record of urine R/E Combi 10 strip test. Results: There were 41(37.3%) males and 69(62.7%) females. The percentage of underweight, normal, overweight and obese students was 31.8%, 36.4%, 22.7% and 9.1% respectively. Out of total females (62.7%), the group overweight (30.4%) and obese (10.1%) was highly significant. (p=0.008). The user students n=48(43.6%) took caffeinated drinks more than 5-7 glasses/week and were found to be significantly obese p=0.17 as compared to non-users n=62(56.4%).Soft drink consumption was significantly associated with proteins appearance in urine (p=0.00) and leucocytes (p=0.17) and the mean PH of urine of soda users was highly significantly acidic (p=0.00) by using combi-10 test strips. Conclusion: Very high sugar contents and other ingredients in soft drinks can be associated with obesity, metabolic and kidney disturbances in young students which in chronic cases exacerbate the condition.